2010
DOI: 10.1074/jbc.m110.107607
|View full text |Cite
|
Sign up to set email alerts
|

DNA Cytosine Methylation in the Bovine Leukemia Virus Promoter Is Associated with Latency in a Lymphoma-derived B-cell Line

Abstract: Bovine leukemia virus (BLV) proviral latency represents a viral strategy to escape the host immune system and allow tumor development. Besides the previously demonstrated role of histone deacetylation in the epigenetic repression of BLV expression, we showed here that BLV promoter activity was induced by several DNA methylation inhibitors (such as 5-aza-2-deoxycytidine) and that overexpressed DNMT1 and DNMT3A, but not DNMT3B, down-regulated BLV promoter activity. Importantly, cytosine hypermethylation in the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 70 publications
1
37
0
Order By: Relevance
“…Accordingly, we have previously reported the absence of DNA methylation in the U3/R region of the YR2 provirus, in opposition to the hypermethylated state of the L267 provirus corresponding region (36). The R/U5 region was partially accessible to nucleases in both models.…”
Section: Discussionmentioning
confidence: 91%
“…Accordingly, we have previously reported the absence of DNA methylation in the U3/R region of the YR2 provirus, in opposition to the hypermethylated state of the L267 provirus corresponding region (36). The R/U5 region was partially accessible to nucleases in both models.…”
Section: Discussionmentioning
confidence: 91%
“…It is thought that silencing of viral expression is a multi-step process leading to the uncontrolled growth of a transformed B-cell clone and the onset of disease [5] and is critical for tumor progression and proliferation of BLV-infected tumor cells [5], as well as escaping recognition by the host immune response [4]. In that sense, the substitution found in the GRE site of the 5′LTR of all BLV strains isolated from the lymphosarcomas might contribute to these factors, since previous studies have shown that substitutions in GRE site significantly reduces basal LTR transcription activity [52] (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…This is thought to be related to the transcriptional repression of viral expression in vivo [3]. Latency is likely a viral strategy to evade the host immune response, thereby allowing tumor development [4,5]. In fact, B lymphocytes harboring an integrated provirus do not produce detectable levels of viral RNA or proteins [6].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have previously reported that 5′LTR hypermethylation is associated with the BLV repression in the true latent L267 cell line but not in the defective latency state present in the YR2 cell line25. Here, we showed by bisulfite genome sequencing that the DNA encoding the BLV miRNA cluster, which is located within a CpG island, was not methylated.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, we have previously demonstrated that the 5′LTR RNA polymerase II-driven transcriptional repression is due to the epigenetic state of the 5′LTR characterized by weak histone acetylation and DNA CpG hypermethylation associated to closed chromatin in a lymphoma-derived BLV-infected L267 ovine cell line harboring a fully competent provirus192125.…”
mentioning
confidence: 99%